Disaster Management During Tropical Storm Karen: The Story of Trinidad Extension - Moses Mike; Ricky Telg; Amy Harder; Jamie Loizzo; Angela Lindsey; Shelli Rampold (Journal of International Agricultural and Extension Education, 2021)
The purpose of this study was to investigate the weather-related disaster preparedness and response strategies of agricultural extension professionals in Trinidad during Tropical Storm Karen (TSK). Trinidad faces perennial flooding, and Trinidad extension professionals have often been involved in the management of weather-related disasters. TSK was contextualized as a case study, and a qualitative approach was used to investigate the lived experiences of the extension professionals who directly assisted with managing the event. Semi-structured interview data were collected, along with concept maps and participant-rendered drawings. Each interview was compared with the participant’s concept map and drawing, while the constant comparative technique was used to evaluate the interview data among the participants to derive themes. Data were collected remotely using internet platforms due to the COVID-19 global pandemic. Findings indicated that disaster preparedness was strategized through field activities, including collecting data and providing disaster advice to clients.Disaster responsiveness was strategized through field actions, primarily through field evaluations for subsidy claims. In addition, related to disaster response, extension professionals faced variouschallenges in responding to TSK, most notably, the inability to access appropriate transportation. The findings of this study can guide the government of Trinidad and Tobago in bolstering the disaster management strategies of the country, as well as inform regional disaster management plans in other Caribbean countries
Keywords: Tropical Storm Karen; disaster preparedness; Trinidad Extension; Caribbean